2004
DOI: 10.1021/jm030485c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Group IVA Cytosolic Phospholipase A2by Novel 2-Oxoamides in Vitro, in Cells, and in Vivo

Abstract: The Group IVA cytosolic phospholipase A(2) (GIVA PLA(2)) is a particularly attractive target for drug development because it is the rate-limiting provider of proinflammatory mediators. We previously reported the discovery of novel 2-oxoamides that inhibit GIVA PLA(2) [Kokotos, G.; et al. J. Med. Chem. 2002, 45, 2891-2893]. In the present work, we have further explored this class of inhibitors and found that the 2-oxoamide functionality is more potent when it contains a long 2-oxoacyl residue and a free carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
153
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(162 citation statements)
references
References 40 publications
4
153
0
5
Order By: Relevance
“…However, due to the fact that AACOCF3 is not exclusively selective for the cPLA2 (Ackermann et al, 1995) and, additionally, a cell lytic activity has been reported (Risse et al, 2002), the various in vivo activities of AACOCF3 must be viewed with caution. Recently, second-generation cPLA2 inhibitors have become available such as 2-oxoamides, which exert potent cPLA2 inhibitory effects in vitro and have proved effective in first in vivo models of inflammation and pain (Kokotos et al, 2004). All these data strongly suggest that cPLA2 is a valid target to treat inflammatory diseases, and, therefore, the development of novel, more selective cPLA2 inhibitors, is of utmost importance.…”
Section: Figurementioning
confidence: 99%
“…However, due to the fact that AACOCF3 is not exclusively selective for the cPLA2 (Ackermann et al, 1995) and, additionally, a cell lytic activity has been reported (Risse et al, 2002), the various in vivo activities of AACOCF3 must be viewed with caution. Recently, second-generation cPLA2 inhibitors have become available such as 2-oxoamides, which exert potent cPLA2 inhibitory effects in vitro and have proved effective in first in vivo models of inflammation and pain (Kokotos et al, 2004). All these data strongly suggest that cPLA2 is a valid target to treat inflammatory diseases, and, therefore, the development of novel, more selective cPLA2 inhibitors, is of utmost importance.…”
Section: Figurementioning
confidence: 99%
“…78-80 °C; 1 H NMR: δ 7.30-7.13 (6H, m, C 6 H 5 , NHCO), 4.11 (1H, m, CH), 3.30 (2H, m, CH 2 NH), 2.60 (2H, t, J = 7.8 Hz, CH 2 C 6 H 5 ), 2.35 (2H, t, J = 6.6 Hz, CH 2 COOH), 1.81-1.47 (8H, m, 4×CH 2 ); 13 C NMR: δ 177.4, 175.5, 142.4, 128.3, 128.2, 125.7, 71.9, 38.4, 35.7, 34.3, 31.4, 31.1, 24.7 Inhibitors 13-18 were prepared as described previously. 28,29 Expression and Purification of Recombinant Group VIA PLA 2 Protein was produced in Sf9 insect cells using a recombinant baculovirus. The virus had been constructed using the cDNA coding for human Group VIA-2 iPLA 2, kindly provided by Dr. Brian Kennedy at Merck-Frost, modified with a six residue histidine tag added three amino acids from the amino terminus using PCR with oligonucleotides 5′-ATGCAGTTCCACCATCACCATCACCATTTTGGAGCGCTGGTCAATACC-3′ and 5′-CCTCAGGGTGAGAGCAGCAGCTG-3′.…”
Section: Saponification Of Methyl Estersmentioning
confidence: 99%
“…In initial work, 2-oxoamides were observed to inhibit inflammation in the rat paw carrageenan-induced edema assay (Kokotos et al, 2004). In the present work, we have focused on the in vivo activity of four related analogs of this series, AX006, AX010, AX048, and AX057.…”
mentioning
confidence: 99%
“…We have reported recently the discovery of a novel structural series of 2-oxoamides that inhibit group IVA cPLA 2 in vitro and in vivo (Kokotos et al, 2002(Kokotos et al, , 2004. In initial work, 2-oxoamides were observed to inhibit inflammation in the rat paw carrageenan-induced edema assay (Kokotos et al, 2004).…”
mentioning
confidence: 99%